Pengaruh Pemuridan terhadap Kedewasaan Rohani Jemaat di Gereja Penyebaran Injil Shalom Belawan - Kristian Andonindo Sitorus; Stasia Daeng Badjie; Marice Saragih; Afriani Manalu; Tirsanika Surbakti (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
Discipleship is one of the church's main strategies in shaping the spiritual maturity of the congregation amidst the challenges of modern life that can cause stagnation in faith growth and weaken spiritual commitment. Through a continuous process of development, discipleship is expected to help the congregation grow in their knowledge of Christ, character, and the practice of living faith in accordance with biblical teachings. This study aims to analyze the influence of discipleship on the spiritual maturity of the congregation at the Shalom Belawan Gospel Spreading Church. The study used a quantitative method with a survey approach. The study population consisted of 40 congregants consisting of 18 men and 22 women aged 17–55 years. Data were collected through questionnaires and analyzed using simple linear regression. The results showed that discipleship had a positive effect on the spiritual maturity of the congregation with a correlation coefficient (R) of 0.339. The coefficient of determination (R²) of 0.115 indicated that discipleship contributed 11.5% to the spiritual maturity of the congregation, while 88.5% was influenced by other factors outside the study. These findings indicate that discipleship plays a role in supporting spiritual growth through ongoing teaching, character development, and faith mentoring. Therefore, churches need to develop planned and systematic discipleship programs to improve the quality of congregational development while strengthening their spiritual maturity.